Analisis Isu-Isu Kritis tentang Pengendalian Mutu Pendidikan di Indonesia pada Sekolah-Sekolah Swasta - DS, Edi Junaidi; Faslah, Romi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the critical issues affecting the quality control of education in private schools in Indonesia. In practice, private schools face various structural and operational challenges, ranging from limited human resources to varying quality of teaching staff to disparities in facilities and infrastructure. Furthermore, internal and external quality assurance mechanisms are not functioning optimally due to a lack of monitoring systems, low compliance with National Education Standards (SNP), and weak school management governance. This study uses a descriptive-analytical approach through a review of literature and education policy documents. The analysis shows that improving the quality of private schools requires strengthening school leadership, enhancing teacher professionalism, improving the accreditation system, and providing more stable funding support. Effective quality control relies not only on government regulations but also on collaboration between schools, foundations, parents, and quality assurance institutions. Therefore, strengthening the quality control system comprehensively is expected to improve the quality of education services in private schools and narrow the gap in education quality in Indonesia. Keywords: Education Quality, private schools, critical issues